Effect of sex and body region on the follicular profile of corriedale sheep - Asiya Kazmi; Sarfaraz A Wani; Asif H Sofi; Masood Saleem Mir; Hilal Musadiq Khan; Zulhuma Muzaffar; A.A. Khan; Basharat Ahmad (Indian Journal of Veterinary and Animal Sciences Research, 2023)
The quality and quantity of wool production is a function of number and type of wool follicles. Hence a study was conducted to evaluate the follicular characteristics of corriedale sheep, a dual purpose breed established well in the temperate climatic conditions of Kashmir valley. Skin samples of corriedale sheep were collected ethically from different body regions viz; neck, shoulder, thorax, flank and back of both sexes and preserved in 10% neutral buffered formalin. The samples were processed for histomorphlogy. Primary and secondary follicle density and their diameter was recorded. Secondary to primary follicle ratio was also calculated. The study revealed the difference in the follicular density and S/P follicle ratio between the sexes as well as between the body regions. In general, the follicle density and S/P ratio was found higher in the flank and thorax region respectively. Evaluation of the follicular profile at flank and thorax during early period will serve as a reliable predictor for the wool yield and quality.